2021
DOI: 10.1186/s12885-021-08628-4
|View full text |Cite
|
Sign up to set email alerts
|

Predicting disease progression in advanced non-small cell lung cancer with circulating neutrophil-derived and platelet-derived microparticles

Abstract: Background Microparticles (MPs) are extracellular vesicles that are associated with cancer development and progression. Advanced non-small cell lung cancer (NSCLC) still shows disease progression after multiple lines of treatment. Therefore, the objective of this study was to explore the correlation between circulating MPs and disease progression in advanced NSCLC, and to find a new method for concise and rapid determination of disease progression. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…176 The transcriptional profile of normal platelets differs from that of platelets isolated from patients with plateletassociated diseases. 177 Based on this evidence, platelets are an attractive platform for cancer diagnosis and prognosis. Specifically, scientists have focused on tumor-educated blood platelets (TEPs) as these platelets changed their F I G U R E 6 Presentation of platelet receptors and intracellular signaling among several kinds of cells.…”
Section: Platelets As a Biomarkermentioning
confidence: 99%
See 1 more Smart Citation
“…176 The transcriptional profile of normal platelets differs from that of platelets isolated from patients with plateletassociated diseases. 177 Based on this evidence, platelets are an attractive platform for cancer diagnosis and prognosis. Specifically, scientists have focused on tumor-educated blood platelets (TEPs) as these platelets changed their F I G U R E 6 Presentation of platelet receptors and intracellular signaling among several kinds of cells.…”
Section: Platelets As a Biomarkermentioning
confidence: 99%
“…The transcriptional profile of normal platelets differs from that of platelets isolated from patients with platelet‐associated diseases 177 . Based on this evidence, platelets are an attractive platform for cancer diagnosis and prognosis.…”
Section: Platelets and Cancer Treatmentmentioning
confidence: 99%
“…The authors speculated that these increased levels of PMPs (as well as those of other biomarkers) were related to CAT in lung cancer patients [82]. In an even more recent study, Liu et al reported that the circulating levels of both PMPs and neutrophil microparticles (NMPs) were increased in treated, advanced NSCLC patients who had progressive disease, as opposed to those with objective remission [83]. They suggested that combining laboratory indices such as these may predict disease progression in lung cancer [83].…”
Section: Pro-tumorigenic Activity Of Platelet Microparticlesmentioning
confidence: 99%
“…As previously referred, the linkage of blood cell derived MVs with the pathogenesis of many diseases has suggested their use as disease biomarkers. In the case of NMVs, their accumulation in blood has been strongly associated with disease severity in sepsis [ 28 , 43 , 44 ], in non-small cell lung cancer [ 45 , 46 , 47 ], and in familial hypercholesterolemia, in which they have been suggested as biomarkers of atherosclerotic plaque burden in asymptomatic patients [ 48 ]. Moreover, their levels can be used as an independent biomarker for the prediction of mortality in infectious endocarditis [ 51 ].…”
Section: White Blood Cell-derived Vesiclesmentioning
confidence: 99%